An Approach to Distinguish between Plasticity and Non-random Distributions of Behavioral Types Along Urban Gradients in a Wild Passerine Bird - Sprau, Philipp; Dingemanse, Niels J. (Frontiers in Ecology and Evolution, 2017)
The impact of urbanization has been widely studied in the context of species diversity and life history evolution. Behavioural adaptation, by contrast, remains poorly understood because empirical studies rarely investigate the relative importance of two key mechanisms: plastic responses vs. non-random distributions of behavioural types. We propose here an approach that enables the simultaneous estimation of the respective roles of these distinct mechanisms. We investigated why risky behaviours are often associated with urbanisation, using an urban nest box population of great tits (Parus major) as a study system. We simultaneously and repeatedly quantified individual behaviour (aggression and flight initiation distance) as well as environmental factors characterizing level of urbanisation (numbers of pedestrians, cars and cyclists). This enabled us to statistically distinguish plastic responses from patterns of non-random distributions of behavioural types. Data analyses revealed that individuals did not plastically adjust their behaviour to the level of urbanization. Behavioural types were instead non-randomly distributed: bold birds occurred more frequently in areas with more cars and fewer pedestrians while shy individuals were predominantly found in areas with fewer cars and more pedestrians. These novel findings imply a major role for behavioural types in the evolutionary ecology of urban environments and call for the full integration of among- and within-individual variation in urban ecological studies.